Cover Image. (14th November 2019) - Dai, Yuxiang; Qi, Yang
Abstract : The cover image is based on the Research Article High‐pressure‐induced phase transition in 1, 3‐diphenylurea: The approaching of N–H⋯O hydrogen‐bonded chains by Yuxiang Dai, Yang Qi., https://doi.org/10.1002/jrs.5706 .